The performance of user verification using two fingerprints based on error rates - Abu Seman, Mohamad Amir; Mohamad Tahir, Hatim; Din, Roshidi (Universiti Utara Malaysia, 2003)
Biometric technologies, especially fingerprint verification, have started to attract users around the world to use it to secure their places or properties.The current implementation of a fingerprint verification system has faced several problems such as noisy finger and fingerprint misplacement by the user. To solve or minimise this kind of problem, the approach using two fingerprints on the verification process has been tried in this research. Two classifiers are used to study the performance level of the system, and compared to the current system that uses a single fingerprint. In this research,total error rate has been used as an indicator to the performance level of the system